Fizik Tedavi ve Rehabilitasyonda Güncel Konular - Akın, Türkan; Parlak, Lütfiye; Kılıç, Zeynep; Tombak, Yasemin; Bozkurt, Sinem; Varman, Büşra; Okçu, Mehmet; İlgü, Olcay and Karaahmet, Özgür Zeliha (Academician Publishing Book DOI Portal, 2023)
-